Pyrolysis Gas Chromatographic Studies on Pyridinium Compounds - K. Sikder, Arun; Sikder, Nirmala (Asian Journal of Chemistry, 2010)
The well known antidotes in the therapy of organophosphorus intoxication, the mono- and bis-pyridinium oximes and their synthetic intermediates have been analyzed by pyrolysis gas chromatography (PGC). The results obtained on PGC at 500ºC and 800ºC indicate that the technique is simple but of restricted applicability in the characterization of the antidotes.